PENGARUH HARGA, VARIASI PRODUK, DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN MELALUI KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING PADA ES TEH POCI DI PRAJEKAN, BONDOWOSO - Febriyanti, Mery Dwi; Arief, Mohammad Yahya; Ediyanto, Ediyanto (Fakultas Ekonomi dan Bisnis, 2025)
Business is an effort to produce and market goods to make a profit. Es Teh Poci is a business engaged in the culinary field under the auspices of PT Poci Kreasi Mandiri. This business is essential for the economy to improve the community's welfare. This study aims to analyze and test the effect of Price, Product Variation, and Service Quality on Consumer Satisfaction through Purchasing Decisions as Intervening Variables on Es Teh Poci in Prajekan, Bondowoso. The population and sample collection method uses the simple random sampling method. Data analysis and hypothesis testing in this study used the Partial Least Squares Structural Equation Modeling (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.2.8 application show that Price has a significant positive effect on Purchasing Decisions, Product Variation has a significant positive effect on Purchasing Decisions, Service Quality has a significant positive effect on Purchasing Decisions, Price has a positive but insignificant effect on Consumer Satisfaction, Product Variation has a negative but insignificant effect on Consumer Satisfaction, Service Quality has a significant positive effect on Consumer Satisfaction, Purchasing Decision has a positive effect on Consumer Satisfaction. The indirect influence hypothesis test results show that the Price variable has a significant positive effect on Consumer Satisfaction through Purchasing Decisions, Product Variation has a positive but insignificant effect on Consumer Satisfaction through Purchasing Decisions, and Service Quality has a significant positive effect on Consumer Satisfaction through Purchasing Decisions.